LITERATURE REVIEW: STAFF PERFORMANCE FACTORS RELATED TO INCOMPLETE MEDICAL RECORD DOCUMENTS IN PUBLIC HEALTH CENTER - Wijayanti, Rossalina Adi; Lestari, Melia Sinta; Deharja, Atma; Santi, Maya Weka (Journal of Public Health Research and Community Health Development, 2024)
Background: Patient medical records are records relating to the patient's identity, diagnosis, action, and to the treatment that has been given to the patient. Thus, medical records must be protected from damage, but damage to medical records is still found in every hospital. Purpose: This study attempts to investigate the causes of damage to hospital medical record materials. Methods: this is literature review, and the research was obtained from google scholar and the portal garuda, using full text articles. The measured results were factors that cause damage to medical record documents. Results: The main factor were still officers with a low level of education, namely high school graduates. This has an impact on filing officers to be not disciplined in maintaining medical record documents, and the absence of implementation of training related to management and storage management in the filing section. The machine factor was that there was no medical record rack available in accordance with the number of medical record documents. The method factor was that there was no SOP for maintaining medical records. The material factor was the raw material for the map using thin paper. The media factor, namely the storage space, has not been avoided from the dangers of water, fire, and biological damage. Conclusion: Based on 5M factors, the factors that have the highest influence on damage to medical record documents are the elements of people, machine, and material. While the factor that causes the least damage to medical record documents is the method.